Diseño y desarrollo del sistema de control de un dispositivo de ejercicio con rodillos para medir y registrar fuerzas durante la propulsión de una silla de ruedas - Aguilera, Francisco; Meza, Mauricio; Nantais, Tom (Revista Mexicana de Ingenieria Biomedica, 2002)
We describe some systems for wheelchair users to exercise while measuring strength and torque, as well as their advantages and disadvantages. We describe a roller system for measurement and matching, as well as the mathematical model used to calculate the torque from the velocity and the angular acceleration in the system. Finally, we describe the control system that was designed for the new system of rollers where each wheel is supported in a pair of rollers, what achieves independence in the measurement between the left and right arms.